Understanding HIV Care Provider Attitudes Regarding Intentions to Prescribe PrEP - Castel, Amanda D. (J Acquir Immune Defic Syndr, 2015)
INTRODUCTION: Pre-exposure prophylaxis (PrEP) is a promising approach to reducing HIV incidence. Thus garnering the support of HIV providers, who are most familiar with antiretrovirals and likely to encounter patients in HIV serodiscordant relationships, to scale-up PrEP implementation is essential. We sought to determine whether certain subgroups of HIV providers were more likely to intend to prescribe PrEP. METHODS: Surveys were administered to HIV providers in Miami, Florida and Washington, DC. Composite scores were developed to measure PrEP knowledge, experience, and likelihood of prescribing. Latent class analysis (LCA) was used to stratify provider attitudes toward PrEP. RESULTS: Among 142 HIV providers, 73.2% had cared for more than 20 HIV-infected patients in the prior 3 months; 17% had ever prescribed PrEP. LCA identified two classes of providers (entropy 0.904); Class 1 (n=95) found PrEP less effective and perceived barriers to prescribing it; Class 2 (n=47) perceived PrEP as moderately effective and perceived fewer barriers to prescribing it. Compared to Class 2, Class 1 had significantly less experience with PrEP delivery (t(22.7)=2.88, p=0.009) and was significantly less likely to intend to prescribe to patients with multiple sex partners (20% vs. 43%, p=0.04) and those with a drug use history (7% vs. 24%, p=0.001). CONCLUSIONS: While most HIV providers found PrEP to be effective, those considering it less effective had limited knowledge and experience with PrEP and had lesser intentions to prescribe. Provider training regarding whom should receive PrEP and addressing potential barriers to PrEP provision are needed if this HIV prevention method is to be optimized.